APPLICATION OF AUTODESK SOFTWARE PRODUCT FOR TRAINING OF STUDENTS IN GENERAL ENGINEERING: APPLICATION OF AUTODESK SOFTWARE PRODUCT FOR TRAINING OF STUDENTS IN GENERAL ENGINEERING - Antonov, Anton (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
One of the most complex and dynamic enterprise systems are logistics. The system designing requires many people, whereas specialized software products can be used to help design different elements and stages. Certain purpose of the work is to be presented software products Autodesk Factory Design Suite and their application in the education of the students in general engineering, which leads to break the traditional way of absorption the material. This cause lasting interest in science, which is a prerequisite for highly qualified personnel, competition in the labor market.